Effects of different internal temperature applications on quality properties of heat‐treated sucuk during production - Armutcu, Ümran; Hazar, Fatma Yağmur; Yılmaz Oral, Zeynep Feyza; Kaban, Güzin; Kaya, Mükerrem (Wiley, 2020)
This study was carried out to determine the effects of different internal temperature (60 degrees C and 68 degrees C) applications on physicochemical and microbiological properties of heat-treated sucuk as well as on volatile compounds and textural properties.Pediococcus acidilacticiS147 strain was used as starter culture. Samples taken during the production stages was analyzed. Analysis of volatile compound profile and instrumental texture properties were carried out in the final product. The production stage factor had a significant effect on of pH, a(w), TBARS, lactic acid bacteria,a* andb* values atp .This factor also had an effect onL* value atp < .05 level. Lactic acid bacteria count and pH value have also been affected from internal temperature application. In contrast, different internal temperature applications did not have very significant effects on volatile compound profile (except acetic acid). About 68 degrees C internal temperature application increased resilience, springiness, and chewiness of samples. Practical applications Heat-treated sucuk is a semi-dry fermented sausage. It is produced by applying three main processes: a short fermentation, heat treatment, and drying. In this study, effects of two different internal temperature applications (60 degrees C and 68 degrees C) on heat-reated sucuk are investigated. According to the results of the research, lactic acid bacteria count decreases significantly when internal temperature is increased to 68 degrees C from 60 degrees C. No significant differences in terms of color is observed. Application of an internal temperature of 68 degrees C increases resilience, springiness, and chewiness values. However, desired properties can generally be provided at both temperatures.